The Influence of Impulsive Buying and Fear of Missing Out on Financial Behaviour: The Role of Financial Literacy as a Moderator - Rizky, Mega; Munawarah; Launa, Noval; Farid, Erwan Sastrawan (Dinasti Publisher, 2025)
The development of technology and social media has driven changes in consumer behaviour, particularly among the younger generation, shifting from conventional to online shopping. the ease of access to online shopping and the emergence of digital payment methods such as e-wallets and pay-later options can trigger impulsive buying behaviour and fear of missing out (FOMO), which in turn impacts individuals' financial behaviour. This study aims to analyze the influence of impulsive buying and FOMO on financial behaviour and explore the role of financial literacy as a moderating variable. This research employs a quantitative approach using a survey method involving 117 Palu City respondents with an income. the data analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), with the help of SmartPLS software. the results indicate that impulsive buying has a positive and significant effect on financial behaviour, while FOMO does not have a significant effect. Additionally, financial literacy does not moderate the relationship between impulsive buying, FOMO, and financial behaviour. these findings suggest that even though individuals may have good financial literacy, self-control remains a crucial factor in financial decision-making. This study contributes to the development of financial literacy by emphasizing cognitive aspects and the importance of strengthening affective aspects such as emotional control and resistance to social pressure.